A photoelectron imaging and quantum chemistry study of the deprotonated indole anion. Issue 22 (29th May 2018) - Parkes, Michael A.; Crellin, Jonathan; Henley, Alice; Fielding, Helen H.
Abstract : Probing the electronic structure of the deprotonated indole anion using photoelectron imaging and quantum chemistry calculations. Abstract : Indole is an important molecular motif in many biological molecules and exists in its deprotonated anionic form in the cyan fluorescent protein, an analogue of green fluorescent protein. However, the electronic structure of the deprotonated indole anion has been relatively unexplored. Here, we use a combination of anion photoelectron velocity-map imaging measurements and quantum chemistry calculations to probe the electronic structure of the deprotonated indole anion. We report vertical detachment energies (VDEs) of 2.45 ± 0.05 eV and 3.20 ± 0.05 eV, respectively. The value for D0 is in agreement with recent high-resolution measurements whereas the value for D1 is a new measurement. We find that the first electronically excited singlet state of the anion, S1 (ππ*), lies above the VDE and has shape resonance character with respect to the D0 detachment continuum and Feshbach resonance character with respect to the D1 continuum.